Validation of the Chinese version of PedsQL™ brain tumor module - Wang, Juan; Li, Jin; Jiang, Xiaofan; Sun, Pei; Li, Xia; Wang, Guanyi (Frontiers in Pediatrics, 2023)
Background: The study introduced the Pediatric Quality of Life Inventory TM (PedsQL TM ) brain tumor module for the first time in China. Further, the Chinese version of the PedsQL™ brain tumor module was developed and its feasibility, reliability, and validity were investigated.A total 129 cases completed the assessment. Feasibility was evaluated according to the percentage of missing items and the time required to complete the questionnaire. Internal consistency, retest reliability, and split-half reliability were tested to confirm reliability. We evaluated validity by testing content validity, construct validity, and criterion-related validity. The consistency between the child-self and parent-proxy reports was analyzed by calculating the correlation coefficient (r value) between them.Results: The Cronbach's alpha values for all subscales were above 0.7 and many subscales scored more than 0.9. The intra-class correlation coefficients of retest reliability were higher than 0.9. The split-half reliability scores for all subscales were higher than 0.6. The factor-item correlations ranged between 0.575-0.922 in the child report and 0.492-0.949 in the parent report. Exploratory factor analyses produced five factors corresponding to each subscale in the child report and six factors in the parent report.The feasibility, reliability, and validity of the Chinese PedsQL TM brain tumor module were ascertained through this study. This module can be used to effectively monitor children with brain tumors and conduct descriptive or exploratory studies to determine the risk factors affecting their quality of life. This would help develop a new basis for formulating measures to improve patient prognosis and quality of life.